2015
DOI: 10.1109/twc.2014.2388213
|View full text |Cite
|
Sign up to set email alerts
|

MGF Approach to the Analysis of Generalized Two-Ray Fading Models

Abstract: We analyze a class of Generalized Two-Ray (GTR) fading channels that consist of two line of sight (LOS) components with random phase plus a diffuse component. We derive a closedform expression for the moment generating function (MGF) of the signal-to-noise ratio (SNR) for this model, which greatly simplifies its analysis. This expression arises from the observation that the GTR fading model can be expressed in terms of a conditional underlying Rician distribution. We illustrate the approach to derive simple ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 34 publications
2
126
0
Order By: Relevance
“…Thus, when N = 0, i.e., no specular component is present, the Rayleigh fading model is obtained, while for N = 1, a single dominant specular component, we have the Rician fading model. The case when there are two dominant specular components, N = 2, is usually referred to as the Two Wave with Diffuse Power (TWDP) fading model or, alternatively, the Generalized Two-Ray with Uniformly distributed phases model (GTR-U) [11]. This model has received increased attention in the last few years, as it contains the aforementioned classical models as particular cases and it accurately fits field measurements in a variety of propagation scenarios [12].…”
Section: Preliminaries and Channel Modelmentioning
confidence: 99%
“…Thus, when N = 0, i.e., no specular component is present, the Rayleigh fading model is obtained, while for N = 1, a single dominant specular component, we have the Rician fading model. The case when there are two dominant specular components, N = 2, is usually referred to as the Two Wave with Diffuse Power (TWDP) fading model or, alternatively, the Generalized Two-Ray with Uniformly distributed phases model (GTR-U) [11]. This model has received increased attention in the last few years, as it contains the aforementioned classical models as particular cases and it accurately fits field measurements in a variety of propagation scenarios [12].…”
Section: Preliminaries and Channel Modelmentioning
confidence: 99%
“…Furthermore of interest are vehicular communication scenarios on highways and motorways, where FD-MIMO beamforming can be employed for multi-user transmission between road-side access points and vehicles as described in [45]. Notice also that channel fading models that contain only two dominant specular components in addition to weak diffuse background scattering, such as the two-wave diffuse power (TWDP), generalized tworay (GRT), and fluctuating two-ray (FRT) fading models [46][47][48][49][50], are well suited to capture the behavior of channel measurements conducted in the millimeter wave band [49,51], suggesting that millimeter wave transmissions are in many cases well characterized by few specular components. Importantly, in the millimeter wave band, even relatively low mobility of users (pedestrians) causes significant time selectivity of the channel due to the small wavelength; hence, CSIT becomes outdated even faster.…”
Section: Targeted Deployment Scenariosmentioning
confidence: 99%
“…However, it has also been found that, in some environments, fading does not follow Rician or Rayleigh distributions but more severe fading than Rayleigh [1] such as the well-known non-stationary behavior of vehicle-to-vehicle channels [2,3,4], where both platforms are mobile in addition to low antenna heights for both ends. Due to complexity of multipath channels, there are still many issues that are not addressed, e.g., proper modeling of fading conditions of variable number of strong components with available diffuse channel components except for few recent results appear in [5,6] and proper modeling of non-stationary channels and how it switches from fading channel type to another.…”
Section: Introductionmentioning
confidence: 99%